2007
DOI: 10.1105/tpc.107.054536
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis MALE STERILITY1 Encodes a PHD-Type Transcription Factor and Regulates Pollen and Tapetum Development

Abstract: The Arabidopsis thaliana MALE STERILITY1 (MS1) gene encodes a nuclear protein with Leu zipper-like and PHD-finger motifs and is important for postmeiotic pollen development. Here, we examined MS1 function using both cell biological and molecular biological approaches. We introduced a fusion construct of MS1 and a transcriptional repression domain (MS1-SRDX) into wildtype Arabidopsis, and the transgenic plants showed a semisterile phenotype similar to that of ms1. Since the repression domain can convert various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
172
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(182 citation statements)
references
References 57 publications
9
172
1
Order By: Relevance
“…Phylogenetic analysis indicates that Arabidopsis MS1, poplar PtMS1, and rice PTC1 form a separate group within the entire family (Ito et al, 2007), suggesting that PTC1 and its close homologs may have a conserved role in plant reproductive development. Consistent with this hypothesis, PTC1 driven by the MS1 promoter is able to rescue pollen wall development and pollen fertility of the homozygous ms1 mutant, suggesting a conserved role regulating programmed anther development in monocot and dicot species (Fig.…”
Section: Ptc1 Plays a Conserved Role In Plant Anther Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic analysis indicates that Arabidopsis MS1, poplar PtMS1, and rice PTC1 form a separate group within the entire family (Ito et al, 2007), suggesting that PTC1 and its close homologs may have a conserved role in plant reproductive development. Consistent with this hypothesis, PTC1 driven by the MS1 promoter is able to rescue pollen wall development and pollen fertility of the homozygous ms1 mutant, suggesting a conserved role regulating programmed anther development in monocot and dicot species (Fig.…”
Section: Ptc1 Plays a Conserved Role In Plant Anther Developmentmentioning
confidence: 99%
“…Also, neither ms1 (Ito et al, 2007) nor ptc1 could be rescued using the equivalent wild-type gene driven by the cauliflower mosaic virus 35S promoter, suggesting that the precise control of MS1/PTC1 expression is critical for pollen development. MS1 expression in the ms1 mutant shows increased expression (Wilson et al, 2001;Yang et al, 2007), suggesting that MS1 is able to negatively regulate its own expression.…”
Section: Ptc1 Plays a Conserved Role In Plant Anther Developmentmentioning
confidence: 99%
“…Pollen wall formation requires exquisite and coordinated spatiotemporal regulation of numerous biosynthetic genes by specific transcriptional regulators (Alves-Ferreira et al, 2007;Ito et al, 2007;Yang et al, 2007). In particular, many genes involved in exine biosynthesis in Arabidopsis have been shown to be repressed by the MS1 transcription factor in wild-type plants and to be overexpressed in the ms1 mutant (Ito et al, 2007;Yang et al, 2007).…”
Section: Genes Involved In Pollen Cell Wall Formation Are Tightly Cormentioning
confidence: 99%
“…In particular, many genes involved in exine biosynthesis in Arabidopsis have been shown to be repressed by the MS1 transcription factor in wild-type plants and to be overexpressed in the ms1 mutant (Ito et al, 2007;Yang et al, 2007). Examination of Arabidopsis microarray data showed that, during development of wild-type and ms1 anthers, several uncharacterized genes are coregulated with genes involved in exine formation.…”
Section: Genes Involved In Pollen Cell Wall Formation Are Tightly Cormentioning
confidence: 99%
See 1 more Smart Citation